2017
DOI: 10.1016/j.celrep.2017.10.077
|View full text |Cite|
|
Sign up to set email alerts
|

Th1-like Plasmodium -Specific Memory CD4 + T Cells Support Humoral Immunity

Abstract: Summary Effector T-cells exhibiting features of either T helper 1 (Th1) or T follicular helper (Tfh) populations are essential to control experimental Plasmodium infection and are believed to be critical for resistance to clinical malaria. To determine whether Plasmodium-specific Th1- and Tfh-like effector cells generate memory populations that contribute to protection, we developed transgenic parasites that enable high-resolution study of anti-malarial memory CD4 T-cells in experimental models. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 79 publications
1
43
0
Order By: Relevance
“…How then are MHC-II-restricted NK1.1 + CD4 + T cells categorized amongst conventional CD4 + T cells and NK-T cells? Our findings indicate that NK1.1 + and NK1.1 − CD4 + T cells are composed of a heterogeneous population of cells expressing markers associated with Th1 and Tfh cells, similar to what has been reported by others ( 21 , 23 , 33 35 ), further supporting the idea that T cells transition through an intermediate state prior to full commitment toward Th1 or Tfh cell differentiation ( 35 ). Perhaps, NK1.1 expression defines one of these intermediate states.…”
Section: Discussionsupporting
confidence: 90%
“…How then are MHC-II-restricted NK1.1 + CD4 + T cells categorized amongst conventional CD4 + T cells and NK-T cells? Our findings indicate that NK1.1 + and NK1.1 − CD4 + T cells are composed of a heterogeneous population of cells expressing markers associated with Th1 and Tfh cells, similar to what has been reported by others ( 21 , 23 , 33 35 ), further supporting the idea that T cells transition through an intermediate state prior to full commitment toward Th1 or Tfh cell differentiation ( 35 ). Perhaps, NK1.1 expression defines one of these intermediate states.…”
Section: Discussionsupporting
confidence: 90%
“…CD49d to examine differences in antigen-experienced CD4 + T cells between WT and Icos -/mice. This approach has been confirmed for viral infection [33] and other models of rodent malaria [34][35][36]. In the absence of CQ, there was a similar percentage and number of CD49d + CD11a + CD4 + T cells in the spleen of WT and Icos -/mice (S1 Fig).…”
Section: Plos Pathogensmentioning
confidence: 61%
“…However, it is likely that TLRs might play an important role in the innate immune response to SARS-CoV-2 infection 42 . Though, we did not use any adjuvants, it is reported that TLRs (TLR3 and TLR4) can effectively bind with spike protein of the CoV 43 . The molecular docking analysis of the CoV-RMEN through HADDOCK showed that the chimeric protein can establish stable protein-protein interactions with TLRs (TLR-3,TLR-4) 41 indicating efficient activation of these surface molecules which is very crucial for immune activation of dendritic cells for subsequent antigen processing and presentation to CD4+ and CD8+ T-cells via MHC-II and MHC-1, respectively corroborating the findings of different earlier studies 11, 20, 21 .…”
Section: Discussionmentioning
confidence: 99%